Penerapan Model Pembelajaran Kooperatif Tipe Rotating Trio Exchange Berbantu Multimedia Interaktif terhadap Hasil Belajar - Mariawati Hasanah; Ahmad Fathoni (Jurnal Pendidikan Informatika (EDUMATIC), 2019)
The purpose of this study was to implement a rotating cooperative learning model of interactive multimedia trio assisted in improving the learning outcomes of class X students of Siti Technology Vocational High School in the 2017/2018 school year. This research method is quantitative and this type of research is pre-experimental with the pre-test and post-test design. The study population consisted of 21 students consisting of 20 students of class X SitiRaudah Technology Vocational School and 1 KKPI subject teacher. The sample consisted of 21 students. To determine the sample of saturated sample engineering research. The instrument for entering data is currently using a test. Data were analyzed using descriptive statistics. Statistical results of the comparison of interactive multimedia assisted rotating exchange type cooperative learning can improve learning outcomes in SitiRaudah Technology X grade X students, the highest with 47 pre-test and post-test 74 tests. Hypothesis test results using t-test samples are presented as smaller than t table with t count 0.00 and t table 0.05 the meaning of the hypothesis is accepted. Consider the process and results of this study, namely researchers who use cooperative learning in the interactive multimedia type rotating exchange trio that allows in correcting KKPI.